Hubungan Perilaku Konsumen dan Pengambilan Keputusan dengan Pembelian Produk Skincare Marwah pada Toko Helviah Gadingrejo - Rafika, Rada; Yenny Marthalena (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
This study aims to determine the relationship between consumer behavior and decision making with the purchase of marwah skincare products at Helviah Gadingrejo Store. The type of research used in this research is descriptive quantitativ.The population in this study are consumers who use marwah skincare. Determining the number of samples using the Slovin formula obtained a sample size of 75 people. The variables studied in this study consist of consumer behavior consisting of social, personal, cultural and psychological factors. Decision making variables consist of problem recognition, information search, evaluation of alternatives, and purchasing decisions. Purchase variable as the dependent variable. The data used in this study were collected using a questionnaire that had previously been tested for its validity and reliability. Analysis of research can be done using pearson correlation analysis.Thus the results of this study state that consumer behavior and decision making with purchases have a positive and significant relationship.